1998
DOI: 10.1016/s0378-1097(98)00416-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential stress gene expression during the development of Neurospora crassa and other fungi

Abstract: Stress genes are differentially expressed during the development of Neurospora crassa and other fungi. Large amounts of constitutive heat shock protein 70 (HSC70) are found in dormant conidia of N. crassa, whereas little mRNA of the related glucose-regulated protein (grp78) is detected. It is, however, not generally clear whether heat shock protein or mRNA is preferentially stored in dormant spores. Germinating spores of N. crassa increase the level of grp mRNA. During this developmental stage, the induction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 40 publications
1
27
0
1
Order By: Relevance
“…Moreover, microscopic analysis revealed that afp::uidA transcription is temporally and spatially regulated during development. This is consistent with the observation that heat shock proteins in Neurospora crassa are dierentially expressed during development and that the interactions between the heat shock transcription factor and HSE dier signi®cantly depending on developmental stage (Rensing et al 1998;Girvitz et al 2000). Developmental cycles in fungi are often controlled by stress-inducing signals.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, microscopic analysis revealed that afp::uidA transcription is temporally and spatially regulated during development. This is consistent with the observation that heat shock proteins in Neurospora crassa are dierentially expressed during development and that the interactions between the heat shock transcription factor and HSE dier signi®cantly depending on developmental stage (Rensing et al 1998;Girvitz et al 2000). Developmental cycles in fungi are often controlled by stress-inducing signals.…”
Section: Discussionsupporting
confidence: 86%
“…Differences in these two forms of dormancy have been studied primarily in model organisms [49,54], but if constitutive dormancy is a common feature across a broad range of fungal taxa [53] and is randomly distributed, it could influence our ability to infer patterns of active community assembly in fungi across environmental gradients.…”
Section: The Role Of Dormancy In Bacterial and Eukaryotic Communitiesmentioning
confidence: 99%
“…Transcription of heat shock genes has been well documented in N. crassa (Britton and Kapoor 2002;Freitag et al 1997;Kapoor et al 1995;Plesofsky et al 2008;Rensing et al 1998;Tremmel et al 2007;Ungermann et al 1994) as well as in other filamentous fungi (Faircloth et al 2009;Fox et al 2007;Georg and Gomes 2007;MonteroBarrientos et al 2008;Rezaie et al 2000;Turkel et al 2006;Xavier et al 1999). However, little is known about the cell stress response to phosphate (Pi) deprivation and changes in extracellular pH.…”
Section: Introductionmentioning
confidence: 99%